Numerical simulation for shell deformation using the Naghdi and Koiter models - Ponte Bejarano, José Luis (2025)
In this research work, shell deformations generated by surface forces acting on the shell are described and simulated. The Naghdi and Koiter models are used to describe shell deformations. A weak formulation for the model is obtained, and some results on the existence of solutions are presented. The finite element method is then used to obtain the deformations. In addition, simulations of shell deformations are shown for the case of sectional curvature k = 0.